Integrating thermal point clouds into BIM-GIS environments: workflow proposal for multi-layer digital twins - Ramón-Constantí, Amanda; Castilla Pascual, Francisco Javier; Garcia de Soto, Borja; Adán-Oliver, Antonio (Frontiers in Built Environment, 2026)
IntroductionThe integration of Thermal Point Clouds (TPCs) into professional Building Information Models (BIM) and Geographic Information System (GIS) workflows is currently hampered by a lack of established methodologies and significant format interoperability challenges. This study addresses this methodological gap by developing and testing integration processes for both BIM and GIS platforms.MethodsTwo proofs of concept were developed using data from a commercial scanner at the New York University Abu Dhabi (NYUAD) campus. For BIM integration, a process was designed to generate open Industry Foundation Classes (IFC) files where average surface temperatures are embedded as native properties of architectural elements. For GIS integration, thermal data was assigned as custom attributes to a manually generated 3D geometric reference model, establishing the preliminary steps for a dedicated thermal-GIS workflow.ResultsThe methodologies were successfully validated through visualization in ArcGIS Pro and ACCA Software GeoTwin. The results demonstrate a tangible path to overcoming current format limitations, enabling the creation of multi-layer thermal digital twins.DiscussionThis approach makes complex thermal data more accessible to Architecture, Engineering, Construction, and Operation (AECO) professionals. By providing a structured workflow for interoperability, the study facilitates improved building management and more accurate energy analysis through the use of integrated thermal digital models.